The APKA a community approach to the education of out-of-school youth - Zoleta, Marcela B. 1945- (1975)
The study describes how the Kilusang Kaisahan ng Kabataan sa Kaunlaran (APKA) meets the manpower needs of the Pasig community. There is a greater demand for operators and/or repairmen of refrigerators/conditioning units, radio/TV sets and cars and embroiderers. APKA conducts its vocational training projects in the barrio elementary schools, barrio health centers and elementary school shops. The organizational set-up of an APKA unit, which is comprised by the Youth Leader, the Cashier, the Storekeeper and Promotion Manager, is adequate for the implementation of the Vocational Training Projects which are financed by the Rizal Development Foundation upon the recommendation of the Pasig Youth Welfare Council.
Thesis (M.Ed.)--University of the Philippines
Keywords: Kilusang, Kaisahan ng Kabataan sa Kaunlaran (APKA).; Vocational education -- Philippines -- Rizal